Rate and factors for scabies recurrence in children in Saudi Arabia: a retrospective study - Anwar E. Ahmed; Hoda Jradi; Doaa A. AlBuraikan; Bashayr I. ALMuqbil; Monirah A. Albaijan; Ali M. Al-Shehri; Hamdan AL-Jahdali (BMC, 2019)
Abstract Background Despite the fact that several scabies outbreaks emerged in schools in Saudi Arabia in 2018, no study has investigated the risk of scabies recurrence among children in Saudi Arabia. This study aimed to estimate the rate of scabies recurrence and identify factors that were associated with an increased risk of recurrence among children. Methods This is a multi-center retrospective study of children (age < 14 years) who were diagnosed between May 20, 2015 and September 12, 2018 with one or multiple recurrent scabies at the Ministry of National Guard Health Affairs (MNGHA) hospitals and clinics in Saudi Arabia. Data were obtained from an electronic health system, BestCare database. Results A sample of 264 children analyzed (mean age of 6.7 years) resulted in a cumulative number of 316 scabies diagnoses in which 86 (27.2%) experienced scabies recurrence (at least once). Independent factors associated with a high risk of scabies recurrence: older children (adjusted hazard ratio [aHR], 1.036; 95% CI, 1.002-1.072; P = 0.039), female gender (aHR, 1.734; 95% CI, 1.329-2.262; P = 0.001), Western region of Saudi Arabia (aHR, 1.548; 95% CI, 1.115-2.151; P = 0.009), and 2nd tertile season [May to August] (aHR, 2.368; 95% CI, 1.706-3.288; P = 0.001). Conclusions The study demonstrated that the recurrence rate of scabies among children is high. Older children, the female gender, the Western region of Saudi Arabia, and the seasonality were independently associated with an increased risk of scabies recurrence. High temperature and low humidity should be explored as leading factors for scabies infestations in Saudi Arabia. Findings derived from this study may be useful for clinicians and governments in optimizing clinical management of scabies cases and contacts.